REFLEKSI SELINTAS TENTANG PRIMORDIALISME, PLURALISME, DAN DEMOKRASI - Taufik Abdullah (Jurnal Masyarakat dan Budaya, 2010)
This writing is a reflective analytical description on the relations between primordialism, pluralism and democracy. By using historical analysis, the writer tries to unfold how the words â€œdemocracyâ€ arose as an idea that led to a social movement. Democracy was used to largely interpreted as â€œmodernismâ€ or â€œdevelopedâ€, which later debates also included the desire for equality of rights and status. This later idea has brought the first social movement against colonialism. By the time Indonesia gained its independence, democracy was thought to be â€“ and can only be achieved â€“ if the people can free themselves from primordial bounds. the imagined democratic community is a community with a social structure and system that is able to bloom a â€œCultural Bazaarâ€ condition, a â€œmarketâ€ that spares room for pluralism. Then, under this conditions, new values can be nurtured as a base to re-create the new society. Keywords: primordialism, pluralism, democracy, historical analysis